Experience Rating, Work Injuries and Benefit Costs: Some New Evidence - Campolieti, Michele; Hyatt, Douglas; Thomason, Terry (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2006)
In 1986, British Columbia’s Workers’ Compensation Board introduced an experience rating program that provided a modest financial incentive for employers to reduce the costs of claims. Using a comprehensive panel data set, we find that claims frequency for health care only and short-term disability claims was reduced following the introduction of experience rating. The introduction of the program did not affect costs for most claim types, except for health care only claims.